PRESUPPOSITION AND IDEOLOGY: A CRITICAL DISCOURSE ANALYSIS OF JOE BIDEN’S INAUGURAL SPEECH - Renaldo, Zainal Arifin (PROJECT (Professional Journal of English Education), 2021)
The 2020 U.S presidential election came with the result of Joe Biden’s victory. This research is aimed at investigating Biden’s ideology manifested in his inaugural speech which was delivered on January 20, 2021. The analysis in this research was conducted under the theory of Critical Discourse Analysis (CDA). In finding the ideology, the researcher worked on the microstructure level by studying the presupposition as proposed by Dijk. The result of this research shows that there are three types of presupposition present in Biden’s inaugural speech i.e. lexical, existential, and factive in which lexical presupposition appear to be the most frequent one. The analysis of the presupposition also result to the finding of Biden’s ideology manifestation towards the issue of immigrants, healthcare, racism, democracy, and climate change.